Adaptasi Pustakawan dalam Menghadapi Kemajuan Teknologi Informasi di Perpustakaan Perguruan Tinggi Bina Sriwijaya - Sari, Aulia Permata; Yoanda, Sely (UIN Raden Intan Lampung, 2022)
Information technology is an information that is formed in detail and simply by going through the delivery process from the sender to the recipient with a fast process. The role of libraries in this information technology era is very helpful for librarians and users. The method used in this study is a qualitative research method using descriptive research and data collection by using interviews, observation and literature review. The object of this research study is Bina Sriwijaya College. Mastery and application of information technology at Bina Sriwijaya College can be said to still use the old way. The use of information technology for user needs is still in the process of digitizing. The development of a digital library or e-library for library management staff can help work in the library through the function of the library automation system.